2019
DOI: 10.3390/cells8101198
|View full text |Cite
|
Sign up to set email alerts
|

Update on the Role of the Non-Canonical Wnt/Planar Cell Polarity Pathway in Neural Tube Defects

Abstract: Neural tube defects (NTDs), including spina bifida and anencephaly, represent the most severe and common malformations of the central nervous system affecting 0.7–3 per 1000 live births. They result from the failure of neural tube closure during the first few weeks of pregnancy. They have a complex etiology that implicate a large number of genetic and environmental factors that remain largely undetermined. Extensive studies in vertebrate models have strongly implicated the non-canonical Wnt/planar cell polarit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
54
2
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 111 publications
(192 reference statements)
0
54
2
9
Order By: Relevance
“…Authors of a recent review list genes containing deleterious rare variants that have been associated with NTDs in humans. This study proffers ANKRD6, CELSR1, CELSR2, CELSR3, DVL2, DVL3, FZD, PK1, VANGL1, VANGL2, LRP6, PTK7, and SCRIB1 as associated genes [68]. Except for DVL2, our study may appear not to corroborate findings in their review.…”
Section: Perspectivecontrasting
confidence: 89%
“…Authors of a recent review list genes containing deleterious rare variants that have been associated with NTDs in humans. This study proffers ANKRD6, CELSR1, CELSR2, CELSR3, DVL2, DVL3, FZD, PK1, VANGL1, VANGL2, LRP6, PTK7, and SCRIB1 as associated genes [68]. Except for DVL2, our study may appear not to corroborate findings in their review.…”
Section: Perspectivecontrasting
confidence: 89%
“…Neural tube closure, which occurs during the fourth week of human gestation, is divided into four distinct phases (Wang et al, 2019). First, a subset of medial ectodermal cells is induced to differentiate into neural progenitors, which form the neural plate.…”
Section: Introductionmentioning
confidence: 99%
“…Scrib is also known for its involvement in planar cell polarity signaling that ultimately regulates embryonic and postnatal development (Montcouquiol et al, 2003(Montcouquiol et al, , 2006aMoreau et al, 2010;Murdoch et al, 2003). Mutations in SCRIB are described in patients with spina bifida (Lei et al, 2013;Robinson et al, 2012;Wang et al, 2019), one of the most common forms of neural tube defect, found at high frequency in patients of Autism Spectrum disorder (ASD) (Dawson et al, 2009;Lauritsen et al, 2002;Timonen-Soivio et al, 2015). Indeed, accumulating evidence suggests a role of SCRIB, together with other polarity genes, in neurodevelopmental and autistic disorders (for review, see (Sans et al, 2016)).…”
Section: Introductionmentioning
confidence: 99%